2010
DOI: 10.1007/s11270-010-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dissolved Forms of Carbon and Inorganic Nitrogen in Small Watersheds of the Coastal Atlantic Forest in Southeast Brazil

Abstract: Based on the fact that streamwater quality reflects landscape conditions, the objectives of this study were: to investigate nitrogen (N), carbon (C), and major ion concentrations in six streams crossing minimally disturbed Atlantic Forest areas, with similar geomorphological characteristics; to determine N and C fluxes in one of these pristine streams (Indaiá); and assess the impact of human activity on the biogeochemistry of two other streams in the same region, crossing urbanized areas. The distribution patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 69 publications
5
33
1
9
Order By: Relevance
“…Several studies reported the impact of land use effect on streams, both in temperate and tropical watersheds (Kamisako et al 2008, Rai et al 2010, Andrade et al 2011. Streams located in undisturbed sites were reported to be more affected by soil characteristics and precipitation, although the streams located in disturbed areas were affected by different sources according to the land use. )…”
Section: Streamwater Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported the impact of land use effect on streams, both in temperate and tropical watersheds (Kamisako et al 2008, Rai et al 2010, Andrade et al 2011. Streams located in undisturbed sites were reported to be more affected by soil characteristics and precipitation, although the streams located in disturbed areas were affected by different sources according to the land use. )…”
Section: Streamwater Chemistrymentioning
confidence: 99%
“…The effects of change in land use on the biogeochemistry have also been described in the literature for both major rivers and streams. It has been shown that these changes affect nitrate, ammonium, calcium, potassium and aluminum concentrations in streams located in temperate (Wang et al 2006, Kamisako et al 2008, Rai et al 2010) and tropical regions (Neill et al 2006, Andrade et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At 100 m the litterfall was equal to 4.0 Mg C ha -1 year -1 , decreasing to 3.4 Mg C ha -1 year -1 at 400 m and further to 2.6 Mg C ha -1 year -1 at 1000 m . The export of carbon (dissolved organic + dissolved inorganic carbon) from rivers and streams was estimated also in the Atlantic Forest of Ubatuba, and it was estimated to be approximately 0.1 Mg C ha -1 year -1 (Andrade et al, 2010).…”
Section: Carbon and Nitrogen Fluxesmentioning
confidence: 99%